Test Physical and Test Irritation Provision Cream Extract Aromatic Ginger ( Kaempferia Galanga L.) - Suhendriyo, Suhendriyo; Dwi Astuti Handayani; Susilo Yulianto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
Galangal rhizome is used in traditional medicine which has effectiveness as an anti-inflammatory and antitoxin. Galangal rhizome contains flavonoids, polyphenols, saponins, essential oils. The content of polyphenols in the form of ethylcinnamate can provide anti-inflammatory effects. The content of saponins, flavonoids, essential oils in galangal rhizome as a treatment for mycosis. The purpose of this study was to determine the results of physical tests and irritation tests of galangal extract cream preparations including organoleptic tests, homogeneity tests, spreadability tests, adhesion tests, pH tests, and irritation tests. The method used in this study was descriptive research, namely to observe the characteristics physical and irritation test results of the cream preparation of kencur rhizome extract. The results of This study is an organoleptic test with dark brown kencur rhizome preparation, semi-solid form, distinctive smell of kencur. The homogeneity test has a homogeneous cream result, the spreadability test result is 4.8 cm, the adhesion test result is 4.78 seconds, the pH test result is 5 and the irritation test of the kencur rhizome extract cream preparation when applied to the respondent's skin does not cause irritation. The results of the physical test that show results that are in accordance with the requirements include organoleptic tests, homogeneity tests, adhesion tests and pH tests. While in tests that do not comply with the requirements, namely the spreadability test, and the results of the irritation test show that the cream does not cause skin irritation reactions when applied.